Systematic Literature Review: Strategi Pembelajaran Kelompok Pendekatan Cooperative Learning untuk Meningkatkan Motivasi, Hasil Belajar, dan Keterampilan Sosial Siswa - Harjun; Sitti Nur Aisah; Muhamad Azmin Fatajaya; Laode Arman Ardian Syah; Ma'alumu; Rosmawati; Annisa Nur Aulia Jamal; Siti Nurmayani; Agis Fauzia; Andi Alyssa Rifka Pratiwi; Sulastri; Wa Ode Zahra Permata (Journal of Literature Review, 2025)
Collaboration and communication skills are key 21st-century competencies that must be developed within educational settings. However, empirical evidence indicates that learning processes in Indonesia are still largely dominated by conventional, teacher-centered approaches, which limit student participation and interaction. This study aims to examine the effectiveness of group learning strategies using the Cooperative Learning approach in enhancing students’ learning outcomes, motivation, and social skills. The research employs a Systematic Literature Review (SLR) method, encompassing three main stages: planning, implementation, and reporting. Articles were gathered from reputable academic databases such as GARUDA, SINTA, and Google Scholar, covering publications from 2017 to 2025, and were rigorously selected based on relevance and methodological quality. The analysis of 20 selected studies reveals that Cooperative Learning consistently improves student engagement, individual responsibility, critical thinking, and teamwork. Nevertheless, its implementation still encounters challenges, including uneven participation among group members, limited instructional time, and teachers’ preparedness in managing classroom dynamics. The study recommends strengthening teachers’ roles as facilitators, integrating digital learning media, and applying diverse Cooperative Learning models such as STAD, TGT, and Jigsaw to foster active, collaborative, and enjoyable learning environments. These findings are expected to provide practical insights for educators in designing adaptive, student-centered learning strategies that align with the demands of modern education.